Development and validation of performance-based assessment instrument in mathematics for senior high schools - Gyamfi, Abraham (University of Cape Coast, 2023)
The purpose of the study was to develop and validate a performance-based assessment instrument in mathematics for Senior High Schools. The study sought to find out if a newly developed performance-based assessment items in mathematics would be a good assessment instrument for Senior High School examination. The study employed quantitative instrumentation research design with a four-phase instrument development and validation process: planning, construction, qualitative evaluations, and quantitative validation. Stratified, census, simple random sampling and purposive sampling procedures were employed to select 240 mathematics examiners, 150 mathematics teachers and 750 SHS Three students in the Western Region for the validation phase of the self-developed instrument. Questionnaire and performance-based assessment test were used as the main data collection instruments. The Cronbach alpha reliability coefficient of the questionnaire was 0.843. Data were analysed using means and standard deviation, Pearson Product Moment correlation coefficient, modified Kappa statistics, Principal Component Analysis and four-way ANOVA. It was found that the performance-based assessment instrument (designed by the author) is feasible and credible, has educational and catalytic effects. It was also found that the developed performance-based assessment has a high inter-rater reliability (0.879-0.988), good content validity ratio (0.834-1.00) and good construct validity. Based on the findings, it was recommended that the performancebased assessment should be an integral part of the methods of assessment lessons in mathematics at the Senior High Schools.
xiv, 271p :,ill
Keywords: Catalytic effect Credibility Differential Item Functioning (DIF) Educational effect Examination malpractice Feasibility Instrument development and validation Mathematics Performance-based assessment Reliability Validity